Relationship between nocturnal blood pressure and 24-h urinary sodium excretion in a rural population in Korea - Shin, Jinho; Xu, Enshi; Lim, Young; Choi, Bo; Kim, Bae; Lee, Yong; Kim, Mi; Mori, Mari; Yamori, Yukio (Clinical hypertension, 2014)
BackgroundThe relationship between sodium intake and blood pressure (BP) is affected by many factors such as absolute level of sodium intake, salt sensitivity, and the accuracy or the timing of the BP measurement. There is no epidemiologic study using both ambulatory BP monitoring (ABPM) and 24-h urine sample in a middle-aged general population. MethodsIn the rural area, Yeojoo County, Gyunggi Province in South Korea, 218 subjects with age between 30 and 59 years old were measured with ABPM and 24-h urine sample. ABPM device was TM2430, and the 24-h urine sample was collected using the aliquot cup. Metabolic syndrome (MetS) score was calculated by the sum of the number of abnormal criteria other than BP. ResultsFor both ABPM and 24-h urine sample, 148 subject data was acceptable for the analysis by the creatinine equation and/or the completeness of collection. Age was 47.4 ± 8.3 years (range 30 to 59 years), and female was 85 (57.4%). In multiple linear regression analysis, sodium intake was not an independent factor for casual BPs and daytime BPs whereas sodium intake was an independent factor for nighttime systolic BP (β = 1.625, p = 0.0026) and nighttime diastolic BP (β = 1.066, p = 0.0017). When compared to the lowest quartiles of sodium intake, daytime diastolic BP and nighttime BPs were in the higher three quartile groups. ConclusionsSodium intake was associated not with casual BPs and daytime BPs but with increased nighttime BPs in the middle-aged general population in Korea BackgroundThe relationship between sodium intake and blood pressure (BP) is affected by many factors such as absolute level of sodium intake, salt sensitivity, and the accuracy or the timing of the BP measurement. There is no epidemiologic study using both ambulatory BP monitoring (ABPM) and 24-h urine sample in a middle-aged general population. MethodsIn the rural area, Yeojoo County, Gyunggi Province in South Korea, 218 subjects with age between 30 and 59 years old were measured with ABPM and 24-h urine sample. ABPM device was TM2430, and the 24-h urine sample was collected using the aliquot cup. Metabolic syndrome (MetS) score was calculated by the sum of the number of abnormal criteria other than BP. ResultsFor both ABPM and 24-h urine sample, 148 subject data was acceptable for the analysis by the creatinine equation and/or the completeness of collection. Age was 47.4 ± 8.3 years (range 30 to 59 years), and female was 85 (57.4%). In multiple linear regression analysis, sodium intake was not an independent factor for casual BPs and daytime BPs whereas sodium intake was an independent factor for nighttime systolic BP (β = 1.625, p = 0.0026) and nighttime diastolic BP (β = 1.066, p = 0.0017). When compared to the lowest quartiles of sodium intake, daytime diastolic BP and nighttime BPs were in the higher three quartile groups. ConclusionsSodium intake was associated not with casual BPs and daytime BPs but with increased nighttime BPs in the middle-aged general population in Korea KCI Citation Count: 1